Fine-scale determination of OH in radiation-damaged zircon using Synchrotron Fourier Transform Infra Red spectroscopy (FTIR) and Attenuated Total Reflectance (ATR) - Van Bronswijk, Wilhelm; Pidgeon, Robert (Elsevier, 2014)
The crystal structure of zircon is gradually broken down by the decay of small amounts of U and Th present in zirconium lattice sites. It has been observed that, with increasing radiation damage, zircon can lose radiogenic Pb and at the same time gain water from the environment. The disturbance of the U-Pb system is a major problem in zircon U-Pb geochronology. Water penetration appears to be an important factor in Pb loss but to explore this further a technique is needed for making fine-scale in situ measurements of water on the polished surface of radiation damaged zircons. Our research has shown that Attenuated Total Reflectance Fourier Transform Infra Red (ATR-FTIR) spectroscopy with a synchrotron source and thermal analysis can be successfully used to map the fine-scale distribution of OH/H2O in radiation damaged zircons. The radiation damaged zircons were found to have an OH/H2O content varying from 0.4% to 5% with maxima occurring in the heavily damaged (metamict) zones noted for their disturbed U-Pb systems. Whilst thermal analysis confirmed the presence of OH and possibly H2O the infrared spectra did not distinguish between them.